(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This in the article Logarithmic inequalities contained of variables some properties using inequalities solve about scientific affairs take going , Logarithmic inequalities of solving one how much methods there is Some cases below shown from the method use much efficiency situation showing to give implied .